Complexo Pioneiros: centro cultural integrado à requalificação do rodoshopping e entorno imediato - Costa, Camila Carvalho (Universidade Federal do Tocantins, 2021)
The present work intends to find an insertion of a cultural equipment in the city of Palmas, specifically in the área located next to the place known as Rodoshopping, which was an important commercial center in the city and is now in a state of abandonment. The Cultural Center will be oriented towards enhancing the collective memory and the city, in order to strengthen the feeling of belonging and identity of the citizens, in addition to bringing more urban vitality to the region, increasing tourism, promoting the requalification of the shopping center and consequently improving the quality of life of Rodoshopping traders.